Network Analysis Approach to Migration Processes - Misheva, Mihaela (Research Papers, 2016)
The study examines international migrations as a network theory object. The research field spreads through the question: What is the analytical potential of network theories in migration? What are the theoretical concepts, key for migrations processes and research? The main thesis of this study is limited to the statement that today network theories are the most appropriate analytical approach to migration with epistemological potential to improve integration through social capital.Network theories allow us to see migration not only through individual decisions of migrating but as a general result - product of interpersonal, interactions, embedded in the economic and political environment; reveals the essence of contemporary migration as a "self-sustaining"; balanced micro and meso level analysis - there is room for a whole range of subjects: family, friends, employers. Reaching also through macro level: remittances, information flow and migration policies.Migrations are placed on a continuum that can be analysed through the social capital of the participants in the migration networks. An attempt was made to present the possibilities for the integration process of social immigrant capital. The analysis is supported by data from: an empirical study on the topic "Social networks and social capital of immigrants in Bulgaria" conducted within the project financed by the Research Activity of University of National and World Economy in 2014, publications of the National Bank of Bulgaria; World Bank researches, data from Eurostat and some basic parameters of the European migration policy, best practices and strategic documents.